Modified Protocols of Aggressive Packet Combining scheme with Consideration of Physical Level Representation for better and smooth data Transmission - Sarkar, Achyuth; Kumar Chakraborty, Swarnendu; Bhunia, CT (International Journal of Computer Sciences and Engineering, 2025)
In this paper, a few schemes are presented to improve the performance of aggressive packet combining scheme (APC). In APC three copies of each packet is transmitted from source to the destination and receiver performs majority logic on the received erroneous copies to extract the correct version. However one of the major drawback of this scheme lies in the fact that it fails to correct the error when erroneous bits are present in two or more transmitted copies or at the same bit location. To overcome these limitations of conventional APC we proposed a new modified version of APC by considering the physical signal through which the transmitted copy can be more efficiently and coherently received by the receiver. Discuss clearly reveals that the proposed scheme is indeed superior to that of conventional APC.